Pattern and Outcome of Heart Failure Amongst Children Admitted in an Emergency Pediatric Unit of a Tertiary Hospital in Sokoto State, North-Western Nigeria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context:Heart failure (HF) is a major cause of mortality in the emergency pediatric unit (EPU). It is the usual presentation of many structural cardiac and non cardiac diseases. An audit of the causes of heart failure is necessary to ensure adequate management and prevention.Aim:We describe the pattern and outcome of children with HF admitted to an EPU of a tertiary hospital in Sokoto.Materials and Methods:This was a cross-sectional study conducted in the EPU over 24 months (May 2019 to April 2021). Children aged 1 month to 15 years admitted with heart failure were recruited consecutively. The demographic characteristics, cause of heart failure, and outcome were entered into a proforma. Data were analyzed using IBM SPSS version 25.Results:One hundred and fifty-five out of 7158 children (2.2%) had HF. Majority of these 103 (66.5%) were aged 1 month to 5 years. The age range was 1–180 months with a mean of 55.4 (±53.7) months and a median of 36 (IQR: 86 months). Males accounted for 84 (54.2%) with a ratio of 1.18:1. The commonest causes of heart failure were congenital heart disease (CHD) 40: 25.8%; severe anemia 34: 21.9%; bronchopneumonia 30: 19.4%; rheumatic heart disease (RHD) 18: 11.6%; and dilated cardiomyopathy 16: 10.3%. There were 45(29.0%) deaths, of which CHD, RHD and severe anaemia accounted for the highest mortality.Conclusion:Structural heart diseases like CHD and RHD, in addition to severe anemia and bronchopneumonia, are significant causes of heart failure and mortality in this environment. A holistic approach to prevention is necessary to reduce the burden.